2018
DOI: 10.1523/eneuro.0465-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Menthol Stereoisomers Exhibit Different Effects on α4β2 nAChR Upregulation and Dopamine Neuron Spontaneous Firing

Abstract: Menthol contributes to poor cessation rates among smokers, in part because menthol enhances nicotine reward and reinforcement. Mentholated tobacco products contain (−)-menthol and (+)-menthol, in varying proportions. We examined these two menthol stereoisomers for their ability to upregulate α4β2 nAChRs and to alter dopamine neuron firing frequency using long-term, low-dose (≤500 nm) exposure that is pharmacologically relevant to smoking. We found that (−)-menthol upregulates α4β2 nAChRs while (+)-menthol does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…In separate investigations, menthol was also determined to act as a noncompetitive antagonist on both α7 and α3β4* nAChRs [ 167 , 168 ]. A combination of computational docking, site-directed mutagenesis, and electrophysiology revealed that menthol may exert its effect on nAChRs by binding to the 9′ position in the transmembrane 2 (M2) helix of nAChRs [ 22 ] ( Figure 4 A). Here, a series of mutations at the 9′ leucine residues (L9′) of the high-sensitivity α4β2 nAChRs were made and characterized with electrophysiology to investigate the connection between menthol’s pharmacology and the L9′ site [ 22 ].…”
Section: Flavoring Chemicals In Nicotine Addictionmentioning
confidence: 99%
See 3 more Smart Citations
“…In separate investigations, menthol was also determined to act as a noncompetitive antagonist on both α7 and α3β4* nAChRs [ 167 , 168 ]. A combination of computational docking, site-directed mutagenesis, and electrophysiology revealed that menthol may exert its effect on nAChRs by binding to the 9′ position in the transmembrane 2 (M2) helix of nAChRs [ 22 ] ( Figure 4 A). Here, a series of mutations at the 9′ leucine residues (L9′) of the high-sensitivity α4β2 nAChRs were made and characterized with electrophysiology to investigate the connection between menthol’s pharmacology and the L9′ site [ 22 ].…”
Section: Flavoring Chemicals In Nicotine Addictionmentioning
confidence: 99%
“…A combination of computational docking, site-directed mutagenesis, and electrophysiology revealed that menthol may exert its effect on nAChRs by binding to the 9′ position in the transmembrane 2 (M2) helix of nAChRs [ 22 ] ( Figure 4 A). Here, a series of mutations at the 9′ leucine residues (L9′) of the high-sensitivity α4β2 nAChRs were made and characterized with electrophysiology to investigate the connection between menthol’s pharmacology and the L9′ site [ 22 ]. It was concluded that menthol’s inhibitory actions rely on the presence of the L9′ site of the M2 helix and only one menthol molecule is sufficient for α4β2 nAChR inhibition.…”
Section: Flavoring Chemicals In Nicotine Addictionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, eliquids are available in many different flavors, and some of the most popular flavors among youth are mint, mango and fruit (Leventhal et al, 2019). The impact of different flavors is only beginning to be determined in preclinical models, with the majority of studies focusing on menthol (Alsharari et al, 2015;Wickham, 2015;Henderson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%